INFLUENCE OF TEMPERATURE ON TRIBOTECHNICAL CHARACTERISTICS OF DETONATION ALLOY COATINGS OF Ge-MP SYSTEM - Щепетов, В. В.; Більчук, Є. Ю. (Proceedings of National Aviation University (archive), 2021)
Comparative results of experimental researches of detonation coverings at the raised temperatures in the conditions of air environment are resulted.